DD-005 Evaluation of interruptions during unit dose drug distribution system in a hospital pharmacy. (25th February 2017) - Tano, M; Roussel, F; Debrix, I; Baud-Camus, F
Abstract : Background: To improve quality and safety of care, multidisciplinary meetings are regularly conducted in order to retrospectively analyse undesirable events in the care system. During one of these experience feedback committees, daily mistakes by pharmacists' assistants (PhA) when filling the trollies with drugs were reported. We formulated the hypothesis that disruptions in the workload may have led to them. In fact, many studies on interruptions (IT) in nursing care have been published. They indicate that interruptions are commonplace and lead to medication errors, particularly during medication administration. Studies about ITs are limited in pharmacy. Purpose: Our study aimed at generating awareness of ITs during daily dispensing in unit dose drug distribution system (UDDS) by PhA. Objectives were to quantify those ITs and understand their causes. Material and methods: We observed 6 of 12 PhA for 20 hours of UDDS. We established an observation grid (1 for each PhA observed) which allowed us to time stamp, and identify causes and authors of each IT (who/when/how/why). Then, we collected PhA opinions through an anonymous questionnaire (6 questions) to asess their feelings about IT. PhA had been informed and had provided consent. The grid was tested twice and then modified. Results: Each observation lasted 1 hour 30 min to 2 hours 30 min. ITs occurred every 8.5 min and lasted 16 min on average, corresponding to 10% of time devoted to UDDS. The frequency of ITs observed (6.9 IT/hour) was similar to the numerous ITs described in nurse stations (6.7 to 7.6 IT/hour). The first cause of distraction was the PhA themselves (41%), initiating conversations. De facto, colleagues (30%) were the second cause due to proximity, then nurses and calls from medical staff (23%). The same types of ITs were observed in nursing stations due to patients' relatives. 10 PhA were questioned and answered they felt disturbed by ITs. Nevertheless, they were particularly understanding of medical staff since their calls are often justified by changes in treatments or discharge of patients. Conclusion: We evaluated ITs to pharmaceutical activity. Half seemed justified to allow collaboration with medical staff. After we identified interruptions, then we made the PhA aware of this and provided recommendations to improve our activity. No conflict of interest